Bridget Jones's baby [videorecording (DVD)] - Thompson, Emma; Thompson, Emma; Zellweger, Renée, 1969-; Firth, Colin, 1960-; Dempsey, Patrick, 1966-; Fielding, Helen, 1958- (Universal Studios Home Entertainment, 2016)
Bridget is forty-something and single again after breaking up with Mark Darcy. She decides to focus on her job and surround herself with old friends and some new ones. But her love life takes a turn when she meets a dashing American named Jack. In an unlikely twist, Bridget finds herself pregnant but she can only be fifty percent sure of the father's identity.